Peran Gaya Kepemimpinan Transformasional Dalam Meningkatkan Kinerja Pegawai Pada Kantor Kecamatan Kota Raja Kota Kupang - Carlyta Saslya; Lende Dangga; Kretisana Jagi (P3M Politeknik Negeri Ambon, 2026)
This study aims to analyze the role of transformational leadership style in enhancing employee performance at the Kota Raja District Office in Kupang City. The study employs a quantitative approach using a survey method. The research population consists of all 20 employees at the Kota Raja District Office; consequently, the entire population served as the study's respondents. Data were collected via questionnaires using a Likert scale and analyzed using simple linear regression and the t-test. The results indicate that transformational leadership style has a positive and significant effect on employee performance. This is evidenced by a calculated t-value of 6.038, which exceeds the t-table value of 2.101 at a 5% significance level (p < 0.05). These findings demonstrate that the better the implementation of transformational leadership by the leadership, the higher the level of employee performance. Leadership practices that provide inspiration, motivation, individual consideration, and intellectual stimulation are shown to contribute to the effectiveness of employee task execution. Therefore, transformational leadership style can serve as an effective strategy for enhancing the performance of civil servants within government agencies. Keywords: transformational leadership style; employee performance